Evolution of Tibial Chondrosarcoma in a Dog - Carvalho, Carina Marchiori; Rahal, Sheila Canevese [UNESP]; Fabris, Viciany Erique [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Mesquita, Luciane dos Reis [UNESP]; Faria, Luis Guilherme de [UNESP] (Univ Fed Rio Grande Do Sul, 2013)
Background: Chondrosarcoma is a malignant neoplasm of mesenchymal origin that generally develops slowly and has a low incidence of metastasis. It was related in dogs, but rarely in small or giant breeds. The most common site of skeletal chondrossarcoma in dogs is the nasal cavity. The lungs are the most common site of metastatic disease, but other organs may be affected. Chondrosarcoma may be classified into primary or secondary according to location in bone, and histologically into mesenchymal and myxoid subtypes. Thus, this study reports the evolution of an uncommon case of chondrossarcoma in a dog's tibia. Case: A 1.4-year-old dog, 58 kg intact-male Brazilian Mastiff was admitted to the veterinary hospital due to lameness and swelling of the stifle region present for 20 days. Radiographic examination showed lytic bone lesions in the proximal third of the right tibia with periosteal reaction, suggestive of bone tumor. Cytological examination revealed inflammatory process indicative of acute periostitis. The clinical signs improved after treatment with nonsteroidal anti-inflammatory (meloxicam, 0.1 mg/kg orally every 24 h) and analgesic (tramadol hydrochloride, 2 mg/kg orally every 8 h) drugs. However, eight months after the initial presentation, the dog had a recurrence of the lameness, and increase in volume and crepitus on palpation of the right knee. Radiographic examination showed cystic lesion located in proximal tibial epiphysis. After curettage of the lesion, the defect was filled with calcium phosphate biomaterial. Cephalexin (30 mg/kg every 12 h orally for 10 days), carprofen (4.4 mg/kg orally every 24 h for 15 days) and chondroitin sulphate (1000 mg orally each 12 h per 30 days) were prescribed postoperatively. The animal showed improvement. At one year after surgery, the dog was presented due progressive weight loss and intermittent lameness of the right hind limb observed for approximately two months. On palpation of the right knee was painful sensitivity and it had a cutaneous nodule three inches. Radiographic examination showed extensive radiolucent cystic area with bone remodeling and periosteal proliferation of the medial aspect of the proximal third of the right tibia. Computed Tomography (CT) demonstrated bone destruction in the proximal portion of the tibia with areas of bone lysis and proliferative irregular reaction, irregular hyperdensity in the medullary region of the right tibia extending to the distal portion of the tibial tuberosity associated with the presence of proliferative periosteal reaction adjacent the bony surfaces, and atrophy of muscles of right hindlimb. Both exams suggested a bone tumor, and bone biopsy was done. The diagnosis was chondrosarcoma. The owner did not authorize the hind limb amputation. Discussion: The diagnosis of chondrosarcoma is based on clinical signs, orthopedic examination findings, radiographic and CT appearance, and cytology. However, definite diagnosis may be obtained only by histopathological examination. Fine needle aspiration samples may contain few cells, and presence of inflammatory process may interfere in diagnosis, as observed in the present case. The tumor is resistant to radiotherapy and chemotherapy. However, surgical removal can be curative, depending upon the location of the chondrosarcoma. Unfortunately, the owner was reluctant to proceed with limb amputation, and the dog was euthanatized after three months of the last evaluation.
Keywords: dog; chondrosarcoma; skeletal; tibia